SIGNIFICANCE OF IMMUNITY INDICATORS IN DETERMINING THE OUTCOME OF CHRONIC VIRAL HEPATITIS D IN PATIENTS - Oblokulov Abdurashid Rakhimovich; Rakhimov To’ymurod Botirovich (Modern American Journals, 2025)
To study the parameters of humoral immunity in patients with liver cirrhosis developed as a consequence of chronic viral hepatitis B with Delta agent, 105 patients with chronic hepatitis D-induced cirrhosis and 62 patients with chronic hepatitis D without cirrhosis were examined. The Ig G level has been recommended as a diagnostic and prognostic immunological marker.
Keywords: Chronic viral hepatitis D, liver cirrhosis, Delta agent, IgA, IgM, IgG, prognosis